A Rare Case Report of a Corpus Callosal Splenial Lesion in the Context of Atypical Neuroleptic Malignant Syndrome - Ryan Serdenes DO; Samuel Orr DO; Pamela Trio MD; Seetha Chandrasekhara MD, MA; Meghan Musselman MD (SAGE Publishing, 2021)
In this report, we describe a case of atypical neuroleptic malignant syndrome (NMS) presenting with an isolated lesion in the splenium of the corpus callosum (ILSCC). There is a paucity of information regarding this topic within the literature and only 7 previous case reports have been published at the time of writing. To our knowledge, this case report is also the first to describe an atypical NMS variant in the context of an ILSCC. In this report, we describe the important considerations in formulating differential diagnosis for ILSCC and are the first report to propose a possible pathophysiological mechanism relating ILSCC with NMS.